2021
DOI: 10.1146/annurev-vision-031021-095225
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Intraocular Pressure

Abstract: Intraocular pressure (IOP) is the cardinal and only modifiable risk factor for glaucoma, the leading cause of irreparable blindness worldwide. Twin and family studies estimate the heritability of IOP to be 40–70%, and linkage studies for IOP have identified numerous loci. Mutations in MYOC can cause markedly elevated IOP and aggressive glaucoma often requiring surgical intervention. However, the majority of the genetic basis for raised IOP and glaucoma in populations is complex, and recent large genome-wide as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…Current glaucoma drugs target lowering IOP. Previous studies using directly genotyped and imputed genetic data have uncovered common and some lowfrequency variants for IOP [1][2][3][4][5][6] . Identifying rare variants that contribute to IOP will help uncover the biological mechanisms regulating this trait and provide improved understanding of IOP regulation and potential therapeutic targets for managing IOP and glaucoma.Genome-wide association studies (GWAS) have identified over 190 genetic loci associated with IOP 1-4 .…”
mentioning
confidence: 99%
“…Current glaucoma drugs target lowering IOP. Previous studies using directly genotyped and imputed genetic data have uncovered common and some lowfrequency variants for IOP [1][2][3][4][5][6] . Identifying rare variants that contribute to IOP will help uncover the biological mechanisms regulating this trait and provide improved understanding of IOP regulation and potential therapeutic targets for managing IOP and glaucoma.Genome-wide association studies (GWAS) have identified over 190 genetic loci associated with IOP 1-4 .…”
mentioning
confidence: 99%
“…Studies have found that the heritability of IOP ranges from 0.35 to 0.67, depending on the study design ( Klein et al, 2004 ; Chang et al, 2005 ; van Koolwijk et al, 2007 ; Carbonaro et al, 2009 ; Zheng et al, 2009 ; Sanfilippo et al, 2010 ; Asefa et al, 2019 ). Identifying genetic factors that contribute to IOP aid in uncovering the biological mechanisms regulating this trait ( Ojha et al, 2013 ; Xu et al, 2021 ), which provides new management avenues for IOP and POAG.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the number of GC patients is expected to reach 111.8 million by 2040 (Allison et al, 2020). There are several known risk factors for GC, such as high intraocular pressure (IOP), a family history, high myopia, and cardiovascular disease (Jonas et al, 2017b; Wang et al, 2021); among which, elevated IOP remains the only recognized risk factor for GC (Xu et al, 2021). A lowering of IOP is also the only method that has been verified as effective for preventing GC progression (Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%